2015
DOI: 10.1002/ajmg.b.32304
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variants in SLC25A12 and risk of autism spectrum disorders: An integrated meta‐analysis

Abstract: The solute carrier family 25 (aspartate/glutamate carrier), member 12 gene (SLC25A12) has been strongly posed as a candidate gene for autism spectrum disorder (ASD) given its important role in mitochondrial function and adenosine triphosphate (ATP) synthesis. Evidence is mounting for the association between SLC25A12 variants (rs2056202 and rs2292813) and ASD risk, but the results are inconsistent. To clarify the effect of these two variants on ASD, a meta-analysis integrating case-control and transmission dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Out of the remaining six articles, two were already in our dataset from the literature search from PubMed. Finally, four articles from the GWAS catalog were manually added to 27 articles previously screened from PubMed, leading to a total of 31 eligible articles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] being included in the systematic review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the remaining six articles, two were already in our dataset from the literature search from PubMed. Finally, four articles from the GWAS catalog were manually added to 27 articles previously screened from PubMed, leading to a total of 31 eligible articles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] being included in the systematic review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of BFDP, five (16.1%) and two (6.5%) comparisons had noteworthy findings (<0.8) at a prior probability of 10 −3 and 10 −6 . Two single nucleotide polymorphisms (SNPs) were found to be noteworthy under FPRP estimation only, and not under BFDP (Comparison T vs. C, SLC25A12/rs2292813 [ 20 ]; C vs. T, SLC25A12/rs2292813 [ 24 ]). In contrast, none of the SNPs were identified to be noteworthy exclusively under BFDP.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies conducted one decade ago reported an association between ASD and SNPs rs2292813, rs2056202 [30][31][32] and rs908670 [33] in the SLC25A12 gene, though a few others found no association between ASD and these SNPs [34,35], including one study conducted within a Han population in Taiwan [18]. Two Recent meta-analyses, including one from our group, summarized studies published before 2014 and both concluded a strong association between SNPs rs2056202 and rs2292813 and ASD [20,36]. With a smaller sample size, we have previously demonstrated a positive association with rs2056202 and rs2292813 and the risk of ASD [22].…”
Section: Discussionmentioning
confidence: 95%
“…The current study included the largest sample size available (total n = 40,681 consisting of 14,821 cases) for a powerful meta-analysis of the DAT1 3′-UTR VNTR gene variants, and used when needed the random-effects model that incorporate heterogeneity among trials (Borenstein et al 2010 ). Indeed, following quality assessment of all included studies according to traditional epidemiological considerations (Liu et al 2015 ) indicated that some studies did not reach high quality scores due to sample size, diagnostic criteria, recruitment strategies and quality control of the genetic analysis. This was reflected in significant heterogeneity, that in some cases, was also confirmed with significant publication bias assessed with Begg’s test (Begg and Mazumdar 1994 ) and Egger’s regression test (Egger et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of all included studies was assessed based on traditional epidemiological considerations for genetic studies as previously described in Liu et al ( 2015 ; Supplementary Table S1). The meta-analysis was conducted using the MIX 2.0-Professional software for meta-analysis in Excel, version 2.0.1.6 ( http://www.meta-analysis-made-easy.com/ ) (Bax et al 2006 ).…”
Section: Methodsmentioning
confidence: 99%